Vitamin D and its relationship to performance and health during a competitive period in elite women's basketball and volleyball players - Álvaro Miguel‐Ortega; Julio Calleja‐González; Juan Mielgo‐Ayuso (Physiological Reports)
Abstract Vitamin D [25(OH)D] is a key nutrient, although its level is often low in the general population. To investigate the relationship between vitamin D levels and muscle performance, and to analyze how vitamin D changes during a 16‐week competitive season and its relationship to the performance tests performed. Participant characteristics: age 25.1 ± 4.7 years; height 1.8 ± 0.1 m, and body mass 73.9 ± 15.4 kg. Vitamin D levels (ng/mL) were at T1 (September): 33.7 ± 14.7 (n = 23), and at T2 (January): 26.1 ± 7.3 (n = 23). Over 16 weeks of competition, participants' blood was analyzed to determine their vitamin D levels. Their athletic abilities were evaluated through various tests: vertical jumps (standing jump and countermovement jump); 20‐m sprint without direction changes; and intermittent endurance test; the vitamin D level decreased from T1 to T2 by −22. 40% [p < 0.05] but performance improved in all tests performed (SJ: 4.57%; CMJ: 6.94%; VO2max: 4.99% [p < 0.05]; 20 m: −1.83%). There is a relationship between vitamin D levels and physical performance in female indoor athletes. The results suggest that increased training load may also negatively affect vitamin D levels in elite female indoor athletes.